Posouzení informačního systému firmy a návrh změn - Záklasník, Martin (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Diplomová práce se zabývá informačním systémem makléřské společnosti. Analyzuje její silné a slabé stránky, popisuje návrh změn včetně realizace vylepšení projektového řízení a v poslední radě popisuje doporučení a vize do budoucna.

The master thesis is focused on the information system of broker company. Analyze its strengths and weaknesses, describes suggest changes, including the implementation of improvements in project management and describes recommendations and visions for the future.
Information System Assessment and Proposal for ICT Modification
Keywords: Informační systém; projektové řízení; Liferay; procesní řízení; Bootstrap; Google Charts; Information system; project management; Liferay; process management; Bootstrap; Google Charts